In search of biohappiness - Swaminathan, M.S (New Jersey, 2011)
This book describes how an era of biohappiness, based on the conservation and sustainable and equitable use of biodiversity, can be launched. It deals with all aspects of conservation such as in situ, ex situ and community conservation, and also covers conservation issues relating to mangroves and other coastal bioresources, whose importance has grown with the emerging possibility of sea-level rise from global warming. The book includes concrete examples of how local tribal families have taken to the establishment of gene, seed, grain and water banks in villages, thus linking conservation, cultivation, consumption and commerce in a mutually-reinforcing manner.
Keywords: Biodiversity